In silico Prediction of Anti-plasmodial Activity of Spices: Targeting Malarial Proteases - Pragya Chaturvedi; Vishakha Raina; Pooran Singh Solanki; Vijay Laxmi Saxena (Journal of Clinical and Diagnostic Research, 2019)
Introduction: Malaria, a tropical disease, caused by Plasmodium is curable; still, the burden of malaria infection exists in third world countries. India, particularly among the South-East Asian region, has the maximum mortality rate. The parasites have developed resistance against antimalarial drugs. Alternatively, plants are the most important and ancient source of the drug and spices, in particular, are being used to treat various ailments. Aim: To identify the effect of common Indian spices in targeting malarial proteases. Materials and Methods: A bioinformatics approach was used to target malarial proteases which exhibit an important role in the erythrocytic cycle of the pathogen by degrading Haemoglobin. Proteases, in particular, Falcipain and Plasmepsin were used to perform docking studies to identify potent molecule for inhibition of malarial progression. Data were collected in the form of structural files from PDB (for protein) and PubChem (for ligands). The Protein structures and ligands were prepared and molecular docking had been done to predict interactions. Results: All the eighteen compounds used in study have shown quite a good affinity with target proteins in the terms of energy (negative binding energy). However, comparatively, interactions of falcipain 2 with thymol and gingerol were almost three times lower than other ligand. Except these, energy ranges were in between 30-40 kilo Joule in negative. Strongest interactions were found in between Plasmepsin 4-piperamide and plasmepsin 2-gingerol. Also, it was found that gingerol was most potent bioactive molecule interacting with almost all proteins as predicted by docking studies. Conclusion: Plasmepsin 2 and Plasmepsin 4 with gingerol and piperamide with highest cdocker energy might indicate the potential of molecules in targeting these proteases. Also, Gingerol was found to be most potent in interacting with malarial proteases.